Age at First Marriage and Fertility Decline in Dabat Health and Demographic Surveillance System Site, Northwest Ethiopia: Decomposition Analysis - Alazbih N; Kaya AH; Mengistu M; Gelaye K (Dove Medical Press, 2021)
Nega Alazbih,1 Assefa Hailemariam Kaya,2 Mezgebu Mengistu,3 Kassahun Gelaye4 1Department of Population Studies, University of Gondar, Gondar, Ethiopia; 2Population Studies, Addis Ababa University, Addis Ababa, Ethiopia; 3Department of Health System and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 4Department of Epidemiology and Biostatistics, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Nega Alazbih Email mihretn21@gmail.comBackground: Fertility decline in Ethiopia has been documented since the 1990s. Amhara National Regional State has recorded the most noticeable fertility decline. However, the specific factors that explain the incipient course of fertility decline in the study area and their relative contributions were not well investigated. Hence, the purpose of this study was to determine contributing factors of fertility decline and to assess variations in fertility that can be attributed to both changes in characteristics and reproductive behaviors of women aged 15- 49 years between 2008 and 2014 in Dabat Demographic and Health Surveillance Site, Northwest Ethiopia.Methods: Cross-sectional censuses were carried out in a Dabat Health and Demographic Surveillance System site in 2008 and 2014. Data for 4,775 and 10,807 women of reproductive age in 2008 and 2014 were used for the analysis. A Poisson regression model was employed to assess the trends of determinants of fertility, and multivariate decomposition analysis was applied to evaluate observed changes in fertility using data from two consecutive cross-sectional censuses of Dabat HDSS.Results: Findings indicated that there was a reduction of an average 640.69 births per 1,000 women of reproductive age during 2014 compared to 2008 in the surveillance site (95% CI=− 669.5 to − 582.4). This overall change in fertility was attributed to both the changing characteristics of women (76%) (95% CI=− 524.74 to − 453.13) and their reproductive behavior (24%) (95% CI=− 224.36 to − 79.14). Drivers of the recent fertility decline were increased age at first marriage, a decreased proportion of currently married women, shift in women's birth to later age, and a higher women's educational status.Conclusion: This study indicated that the overall reduction in fertility was attributed to both changing characteristics of women and their reproductive behavior. Major contributors to the changes in fertility were postponing women's first marriage to a later age and changes in the proportion of currently married women over the study period. Encouraging women to complete at least secondary education is important to increase the age at first marriage and birth, which will in turn accelerate the current fertility transition.Keywords: fertility decline, decomposition, Dabat Health and Demographic Surveillance System, Ethiopia